Amerindian (but not African or European) ancestry is significantly associated with diurnal preference within an admixed Brazilian population. (7th February 2017) - Egan, Kieren J.; Campos Santos, Hadassa; Beijamini, Felipe; Duarte, Núbia E.; Horimoto, Andréa R. V. R.; Taporoski, Tâmara P.; Vallada, Homero; Negrão, André B.; Krieger, José E.; Pedrazzoli, Mário; Knutson, Kristen L.; Pereira, Alexandre C.; et al.
ABSTRACT: Significant questions remain unanswered regarding the genetic versus environmental contributions to racial/ethnic differences in sleep and circadian rhythms. We addressed this question by investigating the association between diurnal preference, using the morningness–eveningness questionnaire (MEQ), and genetic ancestry within the Baependi Heart Study cohort, a highly admixed Brazilian population based in a rural town. Analysis was performed using measures of ancestry, using the Admixture program, and MEQ from 1, 453 individuals. We found an association between the degree of Amerindian (but not European of African) ancestry and morningness, equating to 0.16 units for each additional percent of Amerindian ancestry, after adjustment for age, sex, education, and residential zone. To our knowledge, this is the first published report identifying an association between genetic ancestry and MEQ, and above all, the first one based on ancestral contributions within individuals living in the same community. This previously unknown ancestral dimension of diurnal preference suggests a stratification between racial/ethnic groups in an as yet unknown number of genetic polymorphisms.